Corporate Income Tax Changes in the Context of Earnings Management: a Review of the Literature - Krzeczewska, Olga; Serra Coelho, Luís Miguel (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis: This paper aims to provide a comprehensive review of the theoretical and empirical literature regarding tax-induced earnings management. In particular, the association between anticipated tax changes and earnings management is of interest to the authors. Methodology: This paper uses a systematic literature review to achieve its research objectives. Results of the research: The presented research is mostly devoted to tax rate decreases and focuses on accrual-based earnings management methods. In anticipation of a tax rate change, companies shift their income from a high to a low tax rate period. Moreover, the probability of tax-induced earnings management is higher in case of extreme changes in the tax rate, larger prospects for tax savings as well as in case of private firms. This paper identifies several inconsistencies and gaps in the current literature, emphasizing that the connection between firms’ characteristics, the level of book-tax conformity and the practice of earnings management remains unclear.